Physicochemical, Sensory, and Shelf-Life Characteristics of Probiotic Cream-Filled Snakehead Fish Biscuits with Different Sugars - Jordan Maulana Ma'arif; Dwi Larasatie Nur Fibri; Endang Sutriswati Rahayu (agriTECH, 2026)
The growing interest in functional foods has led to the development of novel probiotic-enriched products. Therefore, this study aims to investigate the effect of different sugar types on the viability of Lactiplantibacillus plantarum subsp. plantarum Dad-13 and the overall quality of probiotic cream-filled biscuits made from snakehead fish flour. The biscuits, filled with a cream formulated from butter, sugar, vanilla paste, soy lecithin, and maltodextrin, were evaluated as a combined product. Quality assessments included probiotic cell viability, shelf-life estimation, sensory acceptability, texture, and chemical composition under storage at 25 °C, 37 °C, and 45 °C for 35 days. The results showed that cane sugar and low-calorie sugar maintained higher probiotic viability (6.06–6.24 log CFU/g at 25 °C) than coconut sugar. Biscuits containing cane sugar had the longest estimated shelf life (up to 2 months at ambient temperature). In addition, sensory evaluation revealed greater panelist preference for biscuits filled with cream containing cane sugar or low-calorie sugar, with overall acceptability scores of 5.53 and 5.26, respectively. These formulations also resulted in reduced hardness, fat, calorie, and sugar contents, while coconut sugar contributed to higher ash content. The findings suggest that cane and lowcalorie sugar are suitable for enhancing the probiotic stability, sensory appeal, and nutritional profile of probiotic cream-filled fish biscuits.